Government Discretionary Authority: Legal Framework and Control Mechanisms in Indonesian Administrative Law - Thio, Ricky; Wagiman, Wagiman; Sibuea, Hotma Pardomuan; Khalimi, Khalimi (Faculty of Law, Universitas Pekalongan, 2024)
This study examines the legal framework and control mechanisms governing government discretionary authority within Indonesian Administrative Law. The research addresses the fundamental challenge of balancing administrative flexibility with legal accountability in the exercise of discretionary power.The research aims to analyze the legal parameters of governmental discretion, examine accountability mechanisms, and evaluate control systems in preventing abuse of authority. This study employs a normative juridical method, utilizing statutory, case law, and conceptual approaches through analysis of legislation, court decisions, and administrative law doctrines.The findings demonstrate that governmental discretion must operate within clear legal boundaries established by administrative law principles and systematic accountability mechanisms aligned with good governance principles. The research reveals significant regulatory gaps in the current framework, particularly in establishing preventive measures against authority abuse. The study identifies the need for strengthened institutional oversight mechanisms while maintaining administrative efficiency.This research contributes to administrative law scholarship by providing analysis of discretionary power boundaries and proposing enhanced control mechanisms that combine legal instruments with monitoring systems in Indonesia's administrative law framework.